Navigating the Insight of Gender Disparity Issues in Tourism: A Conceptual Study - Mitra, Ishita; Sankar, M. Mallika (Atna Journal of Tourism Studies, 2021)
Tourism experience has been perceived traditionally in terms of products, destinations, and consumption patterns. However, modern travelling is seen as an experience, performance, surveillance, play, relationship, and a form of mobility. Research studies in tourism explored gender as a global phenomenon of biased consequence. This paper attempts to conceptualize the agreements relating to ‘tourism is a gender determined activity. Further, investigates the most crucial gender trends affecting tourist destination, like subjectivity and critically examines the premise that destination is actually a perceptual concept, interpreted by consumers and also a result of the moment, the people and motive of their travel.